Analyzing Stock Price Dynamics in the Indonesian Banking Sector: A Study of Technical and Fundamental Factors on the IDX - Dehen Rumbun (Institute of Accounting Research and Novation (IARN), 2023)
This research investigates the intricate relationships between technical and fundamental variables and their influence on stock prices in the Indonesian banking sector on the Indonesian Stock Exchange (IDX). Employing a mixed-methods approach that combines quantitative and qualitative analyses, the study delves into the multifaceted dynamics shaping stock price movements in this critical sector of the Indonesian economy. Quantitative data include historical stock prices, trading volume, and various technical indicators, while qualitative data is collected through interviews with industry experts and banking professionals. The research reveals significant correlations between specific technical indicators, such as moving averages and the Relative Strength Index (RSI), and stock prices. Similarly, fundamental variables like earnings growth, non-performing loan (NPL) ratios, and interest rates exhibit notable associations with stock prices, affirming their impact on market valuations. In the context of existing literature, the research findings align with established theories and empirical evidence, underlining the relevance of both technical and fundamental analysis in understanding stock price movements. The implications of these findings extend to investors, policymakers, financial institutions, market analysts, and the banking industry. Investors can make more informed decisions, manage risks effectively, and optimize portfolio allocations. This research offers valuable insights into the complexities of stock price movements within the Indonesian banking sector on the IDX, providing a foundation for further research and real-time market analysis.